Hemichordate genomes and deuterostome origins - Simakov, Oleg (Nature, 2015)
Sequencing the genomes of two enteropneusts reveals complex genomic organization and developmental innovation in the ancestor of deuterostomes, a group of animals including echinoderms (starfish and their relatives) and chordates (which includes humans).